(untitled) (Journal of actual problems of jurisprudence, 2019)
Given article is dedicated to questions of attraction and recruitment of people for the further exploitation and usage similar to slave labour, as well as legal regulation, stipulating punishment for human trafficking on the example of legislation of Russian Federation. Keywords: legislation, brokers, law, responsibility.